2021
DOI: 10.1021/acs.chemmater.1c03100
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Decomposition Kinetics of Ammonium Perchlorate via Conformal Graphene Coating

Abstract: Ammonium perchlorate (AP) is an oxidizer material that is widely employed in applications ranging from rocketry to airbags. Previous research has suggested that efficient electron transfer plays a critical role in determining the kinetics of catalyzed AP decomposition reactions. Consequently, intimate contact between AP crystals and electron acceptors has the potential to accelerate decomposition kinetics, which motivates the development of conformal coatings with suitably tailored electronic structures. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 41 publications
5
32
1
Order By: Relevance
“…This event had a consistent endotherm enthalpy (ΔH endo ) for all AP composites ranging from 100 to 112 J/g and was comparable to the value reported previously with nitrocellulose-wrapped AP (94−99 J/g). 28 Thus, the result implies that the EC or the wrapping agent (i.e., 2D nanomaterial) does not affect the crystalline structure or phase transitions of AP. A detailed analysis of the powder XRD (PXRD) (Figure S3 Following the orthorhombic to cubic phase transition, the exothermic decomposition of AP was observed.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This event had a consistent endotherm enthalpy (ΔH endo ) for all AP composites ranging from 100 to 112 J/g and was comparable to the value reported previously with nitrocellulose-wrapped AP (94−99 J/g). 28 Thus, the result implies that the EC or the wrapping agent (i.e., 2D nanomaterial) does not affect the crystalline structure or phase transitions of AP. A detailed analysis of the powder XRD (PXRD) (Figure S3 Following the orthorhombic to cubic phase transition, the exothermic decomposition of AP was observed.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Gr−EC−AP had a small, broad peak centered at 300 °C representing LTD, but the peak was much smaller than the LTD peak observed in previous studies with NC used as the wrapping agent. 28 This result implies that the nanomaterial formed from EC and Gr does not have a strong catalytic effect on AP decomposition like that of NC and Gr. 28 In previous work by Secor et al, printed graphene with NC showed enhanced conductivity compared to EC, which is likely the reason for the differences in reactivity for Gr−EC−AP compared to Gr−NC−AP.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…For the LTD process, AP mainly undergoes a gas-solid phase reaction, where generating the intermediate products HClO 4 and NH 3 based on the electron transfer from ClO 4to NH 4 + , which is generally considered to be one of the controlling step 62 . The NC and Co-NPs in Co-NPs@NC-T respectively with high electrical conductivity and partially filled 3d orbital can accelerate the electron transfer process to crack the controlling step 24,48,[63][64][65][66] . In addition, the generated HClO 4 and NH 3 are both adsorbed on the AP surface, which has a chance to undergo a redox reaction with each other.…”
Section: Catalytic Activity and Mechanismmentioning
confidence: 99%
“…For example, literatures have reported that graphene oxide (GO) or reduced graphene oxide (rGO) based composites impart better results than pure PTOs because of the large surface of GO or rGO available during the thermal decomposition of HEMs. [21][22][23][24] The current study employs the citric acid sol-gel method to synthesize BCC, with a focus on producing particles with a narrow particle size. The BCC was then combined with thermally reduced (rGO) to produce BCC/rGO composite.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when combined with metal oxides, the high surface area and reactivity of GO can enhance the catalytic activity of the metal oxides, leading to improved thermal performance. For example, literatures have reported that graphene oxide (GO) or reduced graphene oxide (rGO) based composites impart better results than pure PTOs because of the large surface of GO or rGO available during the thermal decomposition of HEMs [21–24] …”
Section: Introductionmentioning
confidence: 99%